Middle-Range theory of the nursing diagnosis of sedentary lifestyle in young adults - Renata Marinho Fernandes; Ana Carolina Costa Carino; Anna Thays Dias Almeida; Maria Isabel da Conceição Dias Fernandes; Sâmella Karine de Macêdo Leopoldino; Camila Sayonara Tavares Gomes; Ana Raquel Cortês Nelson; Ana Luisa Brandão de Carvalho Lira (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objective: To construct a middle-range theory for the nursing diagnosis of Sedentary Lifestyle in young adults. Methods: A methodological study for the validation of a nursing diagnosis based on a Middle-Range Theory, carried out in six stages: definition of the approach; definition of theoretical-conceptual models; definition of main concepts; development of a pictorial scheme; construction of propositions; establishment of causal relationships and evidence for practice. The theory construction was operationalized through an integrative review and supported by Roy's adaptation model. Results: Three essential attributes were identified; 10 antecedents; 7 clinical consequences; a pictogram, 9 propositions, and 11 causal relationships and evidence for practice. Conclusion: The middle-range theory for the nursing diagnosis of Sedentary Lifestyle in young adults was constructed, expanding the understanding of this phenomenon, to be applied in clinical practice by nurses.